PENATAAN VARIETAS TEBU, SALAH SATU STRATEGI PENTING DALAM PENINGKATAN PRODUKSI GULA NASIONAL - I Ketut Ardana; Deciyanto Soetopo; Syafaruddin Syafaruddin (Perspektif, 2016)
National sugar production of Indonesia was relatively stagnant in the period of (2010-2014) it’s about 2,5 milion ton, due to low produktivity and sugar rendement as well as a big constrain on sugarcane extensification program. Cropping patern arrangement of sugarcane varieties is very important for increasing sugarcane productivity and rendement, to achieve self sufficiency in sugar production and consumption. The proportion of suitable varieties planting in sugarcane areas is unideal, tend to be excesive for late varieties. Principally, landscapping of sugarcane varieties is planting superior varieties of sugarcane (highly productivity and rendement) which appropriate to planting system, maturity character, harvesting time and processing of sugar in sugar manufacture to gain maximum yield. In Indonesia case for period of 2015-2019, the superior varieties should be choosed which having potencial produktivity > 90 ton per ha and rendement > 9 %, for all maturity group of varieties (early, moderate and late), which suitable for areas development of sugarcane. The important step in the near future are (1). Mapping and determining available superior varieties of sugarcane which suitable for planting at the time periods, (2) Producing seeds of superior varieties, (3) Developing areas of sugarcane, intensification of sugarcane cultivation and developing good management of sugarcane manufacture (PG), (4) Supporting research for producing the most superior sugarcane varieties which are more than superior varieties available in Indonesia at the moment., (5) Highly commitment of all stakeholder to apply the program of cropping patern arrangement for sugarcane varieties in all development areas.